Subtitle translation’s role in shaping cross-cultural understanding, interpretation, and audience engagement in chennai express - Ni Putu Lovyta Mai Yoren; I Nyoman Suka Sanjaya; Zanyar Nathir Ghafar; Omar Mohammad-Ameen Ahmad Hazaymeh; Farheen Anjum; Sadia Ayub; Yusuf Sarkingobir (Journal of Education, Social & Communication Studies, 2026)
This study investigates how English subtitle translation shapes cross‑cultural understanding, interpretation, and aesthetic appreciation of the Indian film Chennai Express. Drawing on audio-visual translation theory, especially work on defamiliarization, cultural adaptation, and multimodality, the research examines how subtitles mediate linguistic humour, regional dialects, and culturally loaded references for international audiences. A mixed qualitative design combines multimodal discourse analysis of selected scenes with viewer response questionnaires modelled on cross‑national reception and comprehension studies of subtitled film. Analysis focuses on translation strategies (literal, free, hybrid; domestication vs. foreignization), timing, and stylistic choices, and how these interact with visual and auditory cues to construct meaning and emotion. Findings are expected to show that while subtitles generally secure narrative comprehension across cultures, they also defamiliarize the viewing experience and selectively dilute or reframe culture‑specific humour, social hierarchies, and regional identities. The conclusion argues that high‑quality, culturally sensitive subtitling is crucial for preserving the film’s comic energy and postcolonial cultural textures while enabling global accessibility and intercultural dialogue.